Impact of the Microbiome on the Human Genome. Issue 10 (October 2019) - Jeyakumar, Thiviya; Beauchemin, Nicole; Gros, Philippe
Abstract : Humans live in a microbial world that includes pathogenic bacteria, viruses, and fungi that cause lethal infections. In addition, a large number of microbial communities inhabit mucosal surfaces where they provide key metabolic activities, facilitating adaptation to changing environments. New genome technologies enable both sequencing of the human genome and sequence-based cataloging of microbial communities inhabiting human mucosal surfaces. These have revealed intricate two-way relationships between the microbiome and the genome, including strong effects of human genotypes on the composition and activity of the microbiome. Likewise, the microbiome plays an important role in training and regulating the immune system, and acts to modify expression of human genetic risk for debilitating chronic inflammatory and immune conditions. These studies are suggesting a new role of the microbiome in human health and disease. Highlights: While the selective pressure exerted by pathogens on the human genome is clear, commensal microbes may have also helped humans adapt to changing environments, also leaving marks in the human genome. Affordable genomic sequencing, and cataloging of microbial populations living on humans, is revealing an important human/microbiome interplay in health and disease. The human microbiome plays a critical role in training and regulating the immune system to promote health and fitness. Certain human genetic variants that cause changes in microbial composition are also associated with diseases, suggesting that the microbiome may impact expression of disease-associated genetic variants in humans. The microbiome may thus have influenced the retention or elimination of genetic variants affecting fitness, and may have contributed to sculpting the human genome.